Movement kinematics and cyclic fatigue of NiTi rotary instruments: a systematic review. (26th February 2016) - Ferreira, F.; Adeodato, C.; Barbosa, I.; Aboud, L.; Scelza, P.; Zaccaro Scelza, M.
Abstract: The aim of this review was to provide a detailed analysis of the literature concerning the correlation between different movement kinematics and the cyclic fatigue resistance of NiTi rotary endodontic instruments. From June 2014 to August 2015, four independent reviewers comprehensively and systematically searched the Medline (PubMed), EMBASE, Web of Science, Scopus and Google Scholar databases for works published since January 2005, using the following search terms: endodontics; nickel–titanium rotary files; continuous rotation; reciprocating motion; cyclic fatigue. In addition to the electronic searches, manual searches were performed to include articles listed in the reference sections of high‐impact published articles that were not indexed in the databases. Laboratory studies in English language were considered for this review. The electronic and manual searches resulted in identification of 75 articles. Based on the inclusion criteria, 32 articles were selected for analysis of full‐text copies. Specific analysis was then made of 20 articles that described the effects of reciprocating and continuous movements on cyclic fatigue of the instruments. A wide range of testing conditions and methodologies have been used to compare the cyclic fatigue resistance of rotary endodontic instruments. Most studies report that reciprocating motion improves the fatigue resistance of endodontic instruments, compared to continuous rotation, independent of other variables such as the speed of rotation, the angle or radius of curvature of simulated canals, geometry and taper, or the surface characteristics of the NiTi instruments.